PENERAPAN PENDUGAAN EFISIENSI ALOKATIF PADA USAHATANI BUNCIS (Phaseolus vulgaris, L) - Marthen Robinson Pellokila (Undana Press, 2020)
ABTRACT Efficiency is one of the important indicators to assess the performance of a company or farm. Efficiency guarantees the use of certain inputs to achieve maximum output levels (technical efficiency) and also efficiency ensures the use of certain inputs that maximize profits (price efficiency or allocative efficiency). This article discusses the application of the estimation of price efficiency / allocative efficiency of the use of production inputs in bean farming using the linearized Cobb-Douglas Production function. The results of the analysis shows that the application of price efficiency estimation for production inputs using the Cobb-Douglas production function is satisfactory as long as the classical assumptions required by the multiple regression are fulfilled. Of the five production inputs included in the model, only one production input provides a significant value to production, namely the production input for the land area use. Thus, only the production input for land area use is estimated at the value of its price efficiency. Based on the results of the analysis, it is found that the use of production inputs for land area use has not yet reached its price efficiency.